The Influence of Investment Decisions and Interest Rates on Economic Growth - Ardini, Sarah Fadhila; Juliyaman, Peter; Rani, Dinda Annisa; Fazira, Laila Erra; Jannah, Raihanatul (Economic: Journal Economic and Business, 2024)
This research aims to analyze the influence of investment decisions and interest rates on economic growth in Indonesia. The method used is a quantitative method with multiple linear regression analysis. The data used is secondary data from the Central Statistics Agency (BPS) and Bank Indonesia (BI) for the 2010-2020 period. The research row that investment decisions and interest rates simultaneously do not have a significant effect on economic growth. Partially, investment decisions also have no significant effect, while interest rates have a significant negative effect on economic growth.